2005
DOI: 10.1007/s00125-005-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of protein kinase B/Akt in insulin-induced inactivation of phosphorylase in rat hepatocytes

Abstract: Aims/hypothesis: An insulin signalling pathway leading from activation of protein kinase B (PKB, also known as Akt) to phosphorylation (inactivation) of glycogen synthase kinase-3 (GSK-3) and activation of glycogen synthase is well characterised. However, in hepatocytes, inactivation of GSK-3 is not the main mechanism by which insulin stimulates glycogen synthesis. We therefore tested whether activation of PKB causes inactivation of glycogen phosphorylase. Materials and methods: We used a conditionally active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
(71 reference statements)
2
19
0
Order By: Relevance
“…2). Recent studies have shown that overexpression of a constitutively active form of Akt in rat hepatocytes induces glycogen synthase activity and inhibits glycogen phosphorylase activity (12). Our data provide in vivo evidence that increased Akt activity indeed influences both branches of glycogen metabolism, since in our study hepatic SHIP2 inhibition led to decreased phosphorylation of glycogen synthase and glycogen phosphorylase.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…2). Recent studies have shown that overexpression of a constitutively active form of Akt in rat hepatocytes induces glycogen synthase activity and inhibits glycogen phosphorylase activity (12). Our data provide in vivo evidence that increased Akt activity indeed influences both branches of glycogen metabolism, since in our study hepatic SHIP2 inhibition led to decreased phosphorylation of glycogen synthase and glycogen phosphorylase.…”
Section: Discussionsupporting
confidence: 78%
“…Second, insulin promotes glycogen accumulation by activation of glycogen synthesis, through stimulation of glycogen synthase and reduction of glycogen breakdown, via inhibition of glycogen phosphorylase. The activities of both enzymes are regulated by changes in their phosphorylation states (11), and it has been shown recently that Akt also plays an important role in mediating the inactivation of hepatic glycogen phosphorylase and activation of glycogen synthase (12).…”
mentioning
confidence: 99%
“…The cells were extracted in gel-loading buffer containing 15% sucrose, 2% SDS, bromophenol blue and 1% mercaptoethanol, separated by 10% SDS-PAGE and transferred to nitrocellulose membranes. Membranes were blocked for 2 h in 3% BSA and incubated overnight with a phosphospecific antibody against Akt (protein kinase B) serine 473 (New England BioLabs, Beverly, MA) followed by horseradish peroxidase-linked anti-IgG (Jackson Immunoresearch, Westgrove, PA) [26]. Immunoreactive bands were detected using an enzyme chemiluminescence kit (Amersham Biosciences, Little Chalfont, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Mechanism of inactivation of phosphorylase by α-methyl-5-HT Inactivation of phosphorylase by insulin in hepatocytes occurs downstream of activation of Akt and is associated with phosphorylation of serine 473 [26]. However, α-methyl-5-HT, unlike insulin, did not cause Akt phosphorylation (Fig.…”
Section: -mentioning
confidence: 97%
“…2 Akt plays a critical role in insulin-mediated activation of hepatic glycogen synthase and inactivation of glycogen phosphorylase. 3 Homocysteine is an intermediate in methionine metabolism. Elevated levels of circulating homocysteine, a condition known as hyperhomocysteinemia (HHcy), are an independent risk factor for atherosclerosis.…”
Section: Sismentioning
confidence: 99%